Disjunct perceptions? Climate change threats in two-low lying South African coastal towns - Hoogendoorn Gijsbert; Grant Bronwyn; Fitchett Jennifer M. (Bulletin of Geography. Socio-Economic Series)
Coastal towns rely heavily on the quality and expanse of their beaches to attract tourists. Climate is an important tourism determinant, controlling the length and timing of peak arrivals. South African tourism is particularly reliant on these factors. Perceptions of tourists and tourist accommodation establishment regarding climate change threats to tourism are explored for the towns of St Francis Bay and Cape St Francis. Tourism accommodation establishments were predominantly concerned with day-to-day changes in weather, investing in small-scale infrastructural changes to improve the comfort of their guests. By contrast, tourists demonstrated greater concern for the risk of flooding, sea-level rise and the degeneration of the beaches. This reflects concerning disjunctures between perceptions of tourists and accommodation establishments regarding climate change threats. This may portray to tourists insufficient investment in adaptation at accommodation establishments, resulting in decreased tourist visitations in the short-term in favour of destinations perceived as better prepared.